Strengthening the Smart Policing Legal System in Preventing Digital Radicalization through the Utilization of Big Data and Cyber Surveillance in Indonesia - Bambang Yulianto; Albertus Wahyurudhanto; Kif Aminanto (Journal Customary Law, 2026)
The development of digital transformation has led to the emergence of digital radicalization or cyber radicalization as a new form of threat to national security that develops through social media, encrypted communication, artificial intelligence, and various cyberspace-based digital platforms. This study aims to discuss the threat of digital radicalization from a national legal perspective, examine the weaknesses of conventional cyber surveillance and law enforcement systems in Indonesia, and formulate a legal reconstruction of smart policing based on big data and cyber intelligence in preventing digital radicalization. This study employs a normative juridical method under legislative and conceptual approaches by analyzing various regulations related to cybersecurity, terrorism, personal data protection, and digital law enforcement. The results show that the Indonesian legal system still faces regulatory disharmony, weak integration of authority between institutions, limitations in cyber intelligence, and the absence of a comprehensive legal basis for cyber surveillance, predictive policing, and the use of artificial intelligence in cyberspace surveillance. Therefore, legal reform is needed through the establishment of national smart policing regulations, integration of big data for cybersecurity, strengthening cyber intelligence, institutional harmonization, and the development of an accountable digital surveillance system based on human rights protection. The legal reconstruction is expected to create an effective smart policing system to prevent the spread of digital radicalism while still ensuring the principles of the rule of law, constitutional democracy, and the protection of citizens' privacy rights in Indonesian cyberspace.